Transverse Needling After Autologous Mini-Punch Grafts Improves Repigmentation in Stable Non-Segmental Vitiligo - Ragab M; El zagh O; Farid C (Dove Medical Press, 2021)
Magdy Ragab,1 Omneya El zagh,2 Carmen Farid1 1Department of Dermatology, Venereology and Andrology, Faculty of Medicine, Alexandria University, Alexandria, Egypt; 2Department of Dermatology, Venereology and Andrology, Ministry of Health Hospitals, Alexandria, EgyptCorrespondence: Carmen FaridDepartment of Dermatology, Venereology and Andrology, Faculty of Medicine, Alexandria University, Champollion Street, Al Mesallah Sharq, Al Attarin, Alexandria Governorate, EgyptTel + 00201222966670Fax + 002035925427Email KARMIN.FRED@alexmed.edu.egBackground: Repigmentation remains the primary target in vitiligo treatment. Melanocyte transfer procedures are often required for repigmenting stable, resistant vitiligo lesions necessitating procedural optimization and comparative evaluation. In the current study, we aimed to assess the additive value of weekly transverse needling sessions after mini-punch grafting for repigmenting stable non-segmental vitiligo lesions versus either procedure alone.Methods: Eighty lesions, included in 20 stable non-segmental vitiligo patients, were randomly allocated to each of the three treatment groups (line-1, mini-punch grafting; line-2, needling; and line-3, combined grafting and needling) and to a fourth control group receiving non-procedural treatment (line-4). Oral mini-pulse steroids and narrow-band ultraviolet-B sessions were administered to all patients for 3 months before and 6 months after the interventions. The extent of repigmentation was assessed using planimetry. Secondary outcomes were the time to first repigmentation response, cosmetic matching, and patient satisfaction. Blinding and allocation concealment were not feasible owing to the intervention nature and within subject design.Results: Mini-punch grafting followed by weekly needling for 6 months achieved the fastest response and highest extent of repigmentation. Mini-punch grafts and transverse needling alone provided better results than the control group. No steroid-associated side effects were reported.Conclusion: Weekly needling sessions after mini-punch grafting hastened and improved the repigmentation extent of stable, resistant, non-segmental vitiligo lesions and should be considered during treatment planning.Keywords: vitiligo surgery, oral mini-pulse steroid, planimetry, narrow-band UVB, stability